VARIABILTY OF OIL AND PROTEIN CONTENT IN RAPESEED CULTIVARS AFFECTED BY SEEDING DATE - Balalic, Igor; Marjanovic-Jeromela, Ana; Crnobarac, Jovan; Terzic, Sreten; Radic, Velimir; Miklic, Vladimir; Jovicic, Dusica (Emirates Journal of Food and Agriculture, 2017)
The aim of this study was to determine the variability of oil and protein content in winter rapeseed cultivars affected by seeding date. Four cultivars (Banaćanka, Slavica, Express, Valeska) were sown at six seeding dates (SD1-21 August, SD2-31 August, SD3-10 September, SD4-21 September, SD5-1 October, SD6-9 October) across two cropping seasons. The trial was arranged as Randomized Complete Block Design (RCBD) with four replications. Analysis of variance (ANOVA) showed that the effect of year, cultivar and seeding date were highly significant for oil and protein content. Increased oil content in the second year (2010/2011) was related to weather conditions which were favorable for rapeseed. However, protein content was significantly higher in the first year (2009/2010). Oil content ranged between 41.19% (Valeska) and 42.69% (Express). Significantly lowest oil content across seeding dates was found in SD6 (40.67%), and highest in SD4 (41.86%) and SD1 (41.61%). Valeska showed significantly highest mean protein content (21.54%). Protein content was highest in SD6 (20.18%). Oil content decreased with delayed seeding. Highly significant negative correlation (r = -0.730) existed between oil and protein content. Seeding date had significant influence on oil and protein content in rapeseed. Cultivar Express and SD4 can be pointed out, based on the achieved oil content, and cultivar Valeska for high protein content. Study results may be helpful in recommending optimal rapeseed seeding date in the region.